You are correct. And, here’s why.
First, the “square root” of a number is simply that number raised to the ½ power. For example: 4^½ = 2
If you think about it,it makes sense. There's a rule of exponents that (m^p)^q = m^(pq), so
(4^½)² = 4^[(½)(2)] = 4^1 = 4, If you "square" the "square root" of a number you get the number. Right? Unfortunately it doesn't work so well the other way. That is, (4²)^½) gives you not just 4, butt ±4.
Anyway, because the"square root" is really an exponent (½), it obeys the rules of exponents. The particular rule we’re interested in here is (mn)^p = (m^p)(n^p).
54^½ = (9^½)(6^½)
Since 9^½=3
54^½ = (9^½)(6^½) = (3)(6^½)
Since the problem is (4)(54^½)
(4)(54^½) = (4)( 3)(6^½) = (12)(6^½) or 12√6
2007-05-23 03:14:28
·
answer #1
·
answered by gugliamo00 7
·
0⤊
0⤋
To simplify the square root, you want to factor the number under the square root sign. If you have any pairs of factors that are the same, then you have a square, and they can be extracted from under the square root sign.
In your example, 54 is the number under the square root sign. It can be factored as 2 * 3 * 3 * 3. You have one pair of 3's (and one extra 3), so you can extract a 3 from under the square root sign, leaving you with 6 under the square root sign, and 4 * 3 outside.
Another way of looking at it is:
4 * sqrt(54) = 4 * sqrt(6 * 9) = 4 * sqrt(9) * sqrt(6) = 4 * 3 * sqrt(6) = 12 * sqrt(6)
So your answer is correct.
Hope this helps.
2007-05-23 02:55:38
·
answer #2
·
answered by Geoff L 4
·
0⤊
0⤋
4â54 = 12â6 is correctly simplified, you just look for square numbers inside the root sign
Ex
â180
= â9â20
= â9â4â5
= 3.2.â5
= 6â5
2007-05-23 02:49:04
·
answer #3
·
answered by fred 5
·
0⤊
1⤋
= 4 x â(9 x 6)
= 4 x 3â6
= 12â6 (as you suggest)
2007-05-23 10:36:21
·
answer #4
·
answered by Como 7
·
0⤊
0⤋
factorise 54 = 2* 27 = 2*3^3
for taking square root take one from each pair and leave the unpaired one
2^1- 2^0 taken left 2
3^3 3 (from 3^2) left 3
multiply the things taken 2^0*3^1 = 3
multiply the thing left out 6
so sqrt(54) = 3 sqrt(6)
multiply by 4 to get 4sqrt(54) = 12sqrt(6)
2007-05-23 02:53:07
·
answer #5
·
answered by Mein Hoon Na 7
·
0⤊
0⤋
: 4*(sqrt54)= 4*(sqrt9*6)=4*3: (sqrt6)answer.=12: (sqrt6) yes
2007-05-23 02:49:22
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋